2000
DOI: 10.1046/j.1442-2042.2000.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prazosin, terazosin and tamsulosin in the treatment of symptomatic benign prostatic hyperplasia: A short‐term open, randomized multicenter study

Abstract: Background: The objective of this open randomized clinical study was to compare the short-term efficacy and safety of three alpha-1 blockers, prazosin, terazosin and tamsulosin, in the treatment of lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH). Methods:The study comprised 121 patients with symptomatic BPH who were randomized to receive 0.5 mg of prazosin twice daily, 0.5 mg of terazosin twice daily or 0.1 mg of tamsulosin once daily for the initial 2 weeks. The doses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 13 publications
3
30
0
1
Order By: Relevance
“…These results are consistent with clinical data in which terazosin and doxazosin have been shown to be similarly potent and similarly efficacious agents for the treatment of symptomatic BPH, but with a similar frequency of cardiovascular side effects (Djavan and Merberger, 1999). Interestingly, clinical studies for tamsulosin indicated reduced incidence of cardiovascular side effects compared with terazosin and doxazosin (Lee and Lee, 1997;Djavan and Merberger, 1999;Schä fers et al, 1999;Tsujii, 2000). These observations support the hypothesis that cardiovascular side effects are primarily associated with blockade of ␣ 1b -adrenoceptors, whereas improvement of BPH symptoms is primarily associated with blockade of ␣ 1a -, and perhaps ␣ 1d -adrenoceptors (Testa et al, 1994;Take et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results are consistent with clinical data in which terazosin and doxazosin have been shown to be similarly potent and similarly efficacious agents for the treatment of symptomatic BPH, but with a similar frequency of cardiovascular side effects (Djavan and Merberger, 1999). Interestingly, clinical studies for tamsulosin indicated reduced incidence of cardiovascular side effects compared with terazosin and doxazosin (Lee and Lee, 1997;Djavan and Merberger, 1999;Schä fers et al, 1999;Tsujii, 2000). These observations support the hypothesis that cardiovascular side effects are primarily associated with blockade of ␣ 1b -adrenoceptors, whereas improvement of BPH symptoms is primarily associated with blockade of ␣ 1a -, and perhaps ␣ 1d -adrenoceptors (Testa et al, 1994;Take et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study we compared the PK and PD properties of four ␣ 1 -adrenoceptor antagonists. These included the nonselective antagonists terazosin and doxazosin; the ␣ 1A -/␣ 1D -adrenoceptor-selective antagonist tamsulosin, reported in comparative studies to show uroselectivity (Lee and Lee, 1997;Schä fers et al, 1999;Tsujii, 2000); and a novel ␣ 1A -/ ␣ 1D -adrenoceptor-selective antagonist fiduxosin. PK/PD modeling of these data provide a basis for evaluating the potential uroselectivity of fiduxosin compared with nonselective ␣ 1 -antagonists.…”
mentioning
confidence: 99%
“…2 No studies have been published regarding the use of prazosin in BPH management since the American Urology Association (AUA) published BPH guidelines. 1…”
Section: Resultsmentioning
confidence: 99%
“…The patient characteristic baselines were comparable as shown in Table 1. [Suzuki et al 2001;Okada et al 2000;Na et al 1998;Lee and Lee 1997;Narayan et al 2005;Tsujii 2000;Zhong et al 2000;Hou et al 1999;Jing 1999;Xu et al 2000;Na et al 1996;Lu 1998]. These 12 trials all reported adverse effects including dizziness, severe hypotension, dry mouth.…”
Section: Resultsmentioning
confidence: 99%